Stress-associated radiation effects in pygmy wood mouse Apodemus uralensis (Muridae, Rodentia) populations from the East-Urals Radioactive Trace. (2nd September 2016) - Orekhova, Natal'ya A.; Modorov, Makar V.
Abstract: This work is based on the comparative analysis of data obtained in the course of monitoring pygmy wood mouse populations ( Apodemus uralensis Pallas, 1811) in the East-Urals Radioactive Trace (EURT) area and background territories. The effect of population size and its interaction with the radioactivity on biochemical parameters in the spleen and adrenal glands was studied. The concentrations of total lipids, proteins, DNA and RNA, activity of glucose-6-phosphate isomerase and catalase as well as the level of lipid peroxidation (LPO) were evaluated. The functional-metabolic shifts seen with large population sizes were characterized by delipidisation of adrenocortical cells, increased LPO as the main mechanism for steroidogenesis, growth of the protein components of the adrenal glands to maintain their hyperfunction, as well as immunosuppression associated with the restriction of carbohydrates providing splenocytes, reduction of DNA synthesis, and the development of a pro-/antioxidant imbalance. Reactivity of the neuroendocrine and hematopoietic systems of animals experiencing a high population density was higher in the EURT zone compared with the reference group. This difference can be explained by the additional stress from the chronic radiation exposure. The level of LPO, catalase activity, and DNA/protein ratio in the spleen and the total protein content in the adrenal glands were the most sensitive to the interaction of population size and radiation exposure. The harmful effect (distress) of the interaction of non-radiation and radiation factors can manifest when there is a population abundance above 30 ind./100 trap–day and a radiation burden which exceeds the lower boundary of the Derived Consideration Reference Levels, which is above 0.1 mGy/day.